An evaluation of astaxanthin as a nutraceutical growth promoter in starter diets for weanling pigs - Bergstrom, J.R.; Nelssen, Jim L.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A nursery study was conducted at the KSU Swine Teaching and Research Farm to evaluate the effect of increasing dietary astaxanthin (0, 5, 10, and 25 ppm) on weanling pig performance. Astaxanthin is a carotenoid found in various plants, algae, and seafood that exhibits antioxidant and potential anti-inflammatory properties that may be beneficial during times of stress and reduced immunity, such as weaning. A total of 210 pigs (initially 12.6 lb) were used in the 28-d experiment. Pigs were blocked by weight and randomly allotted to one of five dietary treatments. Pigs were fed simple corn-soybean meal-dried, whey-based diets during Phase 1 (d 0 to 14); and corn-soybean meal diets in Phase 2 (d 14 to 28). Treatments consisted of a basal diet for each phase without added feed-grade antibiotic, or the basal diet with 5, 10, or 25 ppm added astaxanthin without added feed-grade antibiotic; or the basal diet with a feed-grade antibiotic (Neo-Terramycin with 140 g of neomycin and 140 g of oxytetracycline per ton). For the d 0 to 14 (Phase 1) period, ADG and F/G were improved (P<0.05) by including a feed-grade antibiotic in the diet. Average daily gain and F/G of pigs fed astaxanthin was not different than control pigs. Pigs fed a feed-grade antibiotic during Phase 1 were heavier (P<0.05) on d 14 than were pigs fed 0, 5, or 10 ppm astaxanthin. They also tended to be heavier (P<0.10) than pigs fed 25 ppm astaxanthin. For the overall Phase 2 period (d 14 to 28), pigs fed antibiotic had greater (P < 0.05) ADG than pigs fed 0, 5, and 25 ppm astaxanthin; the pigs fed 10 ppm astaxanthin had intermediate ADG. Pigs fed antibiotic had greater (P<0.05) ADFI than pigs fed all other treatments. Feed efficiency was improved (quadratic, P<0.07) as the level of astaxanthin increased to 10 ppm and then returned to control values at the 25 ppm level. Pigs fed antibiotic had poorer (P<0.05) F/G than pigs fed 0, 5, or 10 ppm astaxanthin, and pigs fed 25 ppm astaxanthin had poorer (P<0.05) F/G than pigs fed 10 ppm astaxanthin. Overall (d 0 to 28), ADG, ADFI, and average weight on d 28 were improved (P<0.05) by including a feed-grade antibiotic in the diet. Pigs fed 25 ppm astaxanthin or a feed-grade antibiotic had poorer (P<0.05 and P<0.10, respectively) F/G than pigs fed 10 ppm astaxanthin. In conclusion, the growth performance of pigs receiving 5, 10, or 25 ppm of astaxanthin in the Phase 1 and Phase 2 diets was not different than that of pigs fed the negative control diet. However, ADG and ADFI were improved by including a feed-grade antibiotic in the Phase 1 and Phase 2 diets.
Keywords: Swine; Antibiotics; Astaxanthin